Endogenous Endophthalmitis Associated with Liver Abscess Successfully Treated with Vitrectomy and Intravitreal Empirical Antibiotics Injections - Sung Woong Lim; Youngje Sung; Hee Jung Kwon; Won Kyung Song (Case Reports in Ophthalmological Medicine)
Purpose. Klebsiella pneumoniae is the most common pathogen of endogenous endophthalmitis accompanying liver abscess in East Asia. The treatment may be different for the patients with endogenous endophthalmitis from the postoperative endophthalmitis. Prompt administration of both intraocular (vancomycin and ceftazidime) and systemic (ceftriaxone, aminoglycoside, and/or metronidazole) antibiotics have been a mainstay of treatment. However, ceftriaxone has been proven to more effectively kill K. pneumoniae than ceftazidime in in vitro studies, and the safety of intravitreal ceftriaxone has been confirmed in animal studies. Methods. Two diabetic female patients with liver abscess presented with decreased visual acuity of the unilateral eyes. Fundus photography, ocular ultrasonography, and abdominal computed tomography were performed. Results. A 50-year-old diabetic female patient with liver abscess presented decreased visual acuity of the left eye. In fundus examinations, a yellowish necrotic lesion was noted throughout the eye. The results of culture of the blood culture was positive for K. pneumoniae. She was successfully treated with intravitreal ceftazidime injections, and the remaining vitreous opacity was treated with vitrectomy. A 62-year-old female with liver abscess presented a visual symptom of floaters in the right eye. The fundus had a hazy appearance through the vitreous opacity. A yellowish-white subretinal abscess was noted at the temporal macula. Cultures of blood were negative. She underwent intravitreal injections of empirical antibiotics. However, she did not respond to intravitreal vancomycin and ceftazidime. Thus, we changed the intravitreal antibiotics from ceftazidime to ceftriaxone and performed vitrectomy. Her ocular status significantly improved after this change. Conclusion. Our results indicate that for cases with EE, prompt initial treatment with broad spectrum antibiotics, followed by rapid use of antibiotics selected according to culture results, and empirical use of antibiotics in cases of a negative culture may be an effective treatment. Vitrectomy also can be an effective treatment option for vitreous opacity refractory to the treatment.